CUSTOMER RETENTION STRATEGIES AT HYPERMARKETS IN JAKARTA - Willy Arafah (Universitas Trisakti, 2010)
Today many Hypermarket growing in Jakarta, although Jakarta market is very large and seems very promising, Hypermarkets are finding it tough to be profitable in Jakarta. One of the marketing strategies is to focus on retaining the existing customer as they are three time more profitable than looking for the new one. In this research we examine the factor that influence customer intention to continue purcjhasing from Hypermarkets in Jakarta. The results show that customer’s perceived value is an important indicator of customer continuance intention, as are the loyalty incentives provided by the Supermarkets. Moreover, convenience is more important for customer in these markets than enjoyments. Hypermarkets can increase customer retention by focusing their strategies in making customer experience more valuable and convenient. Implication for theory and practice are also discusses in this research